The evaluation of serum N-terminal prohormone brain-type natriuretic peptide, troponin-I, and high-sensitivity C-reactive protein levels in children with congenital heart disease. (November 2014) - Uner, A; Doğan, M; Ay, M; Acar, Ç
Although advanced diagnostic and treatment methods are available, congenital heart disease (CHD) holds an important place among the causes of death within the first year of age. Therefore, several prognostic factors are needed for diagnosis and monitoring of these patients. In this study, which includes 66 CHD patients and 38 healthy control children, serum cardiac troponin-I (cTnI), high-sensitivity C-reactive protein (Hs-CRP), and N -terminal prohormone brain-type natriuretic peptide (NT-proBNP) levels were analyzed for their prognostics values. The patient groups were categorized and then evaluated as cyanotic ( n = 16), acyanotic ( n = 50), symptomatic ( n = 23), asymptomatic ( n = 43), and isolated ventricular septal defect (VSD)-isolated atrial septal defect (ASD) groups. Cyanotic group was statistically compared with acyanotic group, symptomatic group with asymptomatic group, and VSD group with ASD group. Between the cyanotic, acyanotic, and control groups; between symptomatic and asymptomatic groups; and between the VSD and ASD groups, significant difference was not showed for age ( p > 0.05). NT-proBNP was found to be significantly higher in the cyanotic group than acyanotic and control group, in the symptomatic group than asymptomatic group; and in the patient group than healthy control group ( p < 0.05). Between the groups of VSD and ASD, significant difference was not showed ( p > 0.05). The same comparison results for TnI and Hs-CRP were not significant ( p > 0.05). TnI and Hs-CRP were only found significantly higher in the patient group than healthy control group ( p < 0.05). Eventually, we think that NT-proBNP, Hs-CRP, and TnI might be used for clinical management and estimation of outcome of these disorders in the future and these also might be able to modify existing strategies, but much more studies are needed.